Objective evaluation of anosmia and ageusia in COVID‐19 patients: Single‐center experience on 72 cases. Issue 6 (29th April 2020) - Vaira, Luigi Angelo; Deiana, Giovanna; Fois, Alessandro Giuseppe; Pirina, Pietro; Madeddu, Giordano; De Vito, Andrea; Babudieri, Sergio; Petrocelli, Marzia; Serra, Antonello; Bussu, Francesco; Ligas, Enrica; Salzano, Giovanni; et al.
Abstract: Background: The first European case series are detecting a very high frequency of chemosensitive disorders in COVID‐19 patients, ranging between 19.4% and 88%. Methods: Olfactory and gustatory function was objectively tested in 72 COVID‐19 patients treated at University Hospital of Sassari. Results: Overall, 73.6% of the patients reported having or having had chemosensitive disorders. Olfactory assessment showed variable degree hyposmia in 60 cases and anosmia in two patients. Gustatory assessment revealed hypogeusia in 33 cases and complete ageusia in one patient. Statistically significant differences in chemosensitive recovery were detected based on age and distance from the onset of clinical manifestations. Conclusion: Olfactory and gustatory dysfunctions represent common clinical findings in COVID‐19 patients. Otolaryngologists and head‐neck surgeons must by now keep this diagnostic option in mind when evaluating cases of ageusia and nonspecific anosmia that arose suddenly and are not associated with rhinitis symptoms.